European integration and regional business cycles - a test for the Spanish case - Juan R. Cuadrado-Roura; Tomás Mancha-Navarro; Rubén Garrido-Yserte (European Regional Science Association (ERSA), 2002)
It is a well-known fact that economic integration processes tend to link business cycles among participating economies. Strengthening of commercial relationship, changes in direct investment patterns, capital flows, etc. contribute to explain this progressive coincidence of economic fluctuations. The aim of this contribution is to show empirical evidence of this cyclical pattern at regional level. Nevertheless, what could be true at national level may differ when considering regions: regional business cycles can show convergence or divergence patterns simultaneously. Using Regio date base and National Accounts figures referred to a group of EU regions, the paper will be focused to analyse if the European integration process have led to more regular (synchronised) business cycles. Some explanatory variables of these results will be tested and some policy recommendations could be derived from the findings.
Keywords: 330